Dielectric Properties of Barium Zirconate Titanate Ceramics Prepared using Hydrothermal Method - Ismail, Mukhlis M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Barium titanate (BT) with different content of Zr (0.001 and 0.008) is prepared using hydrothermal method at 150oC for 2h. It is found that with increased of Zr content, the lattice constant a increases while the lattice constant c decreases. It is observed also that the curie temperature peak shift to lower temperature and be broadened. The lattice constants have the same value at Zr content equal to 0.027. For BT samples sintered at 1000oC, the dielectric constant below Curie temperature is about 2000 and becomes 6000 at Curie temperature. With the increased of sintered temperature (1200oC), the dielectric constant is about 4000 and becomes 9600 at Curie temperature (Tc). At Curie temperature the dispersion in BZT1 (x=0.001) is distinct than that of pure BT. At near T1 (temperature at phase transition from tetragonal to orthorhombic) the little broadening is observed of BZT1 in comparing with BT. The dispersion of BZT2 (x=0.008) is more distinct than that of BZT1 (x=0.001) and BT. After adding gradual increasing of Zr, both T1 (tetragonal to orthorhombic phase transition) and Tc are shifting to each other.
Keywords: Hydrothermal method; Dielectric constant; BT BZT